Clinically assessed posttraumatic stress in patients with breast cancer during the first year after diagnosis in the prospective, longitudinal, controlled COGNICARES study. Issue 1 (22nd February 2016) - Voigt, Varinka; Neufeld, Franziska; Kaste, Judith; Bühner, Markus; Sckopke, Philipp; Wuerstlein, Rachel; Hellerhoff, Karin; Sztrókay‐Gaul, Anikó; Braun, Michael; von Koch, Franz Edler; Silva‐Zürcher, Eliane; Hasmüller, Stephan; et al.
Abstract: Objective: There is ongoing debate whether cancer qualifies as traumatic stressor. We investigated prevalence and course of posttraumatic stress in patients with early breast cancer (BC) during their first year after diagnosis and determined effects of mastectomy and chemotherapy. Methods: Patients with stage 0–III BC aged ≤65 years were evaluated with the Structured Clinical Interview for DSM‐IV modules for acute and posttraumatic stress disorder (ASD and PTSD, respectively) before treatment, after chemotherapy, and 1 year after diagnosis. Matched controls were assessed at matched intervals. Effects of time, mastectomy, and chemotherapy on BC‐related PTSD symptom severity were tested with linear mixed model analysis. Results: Stress disorder (ASD or PTSD) related to BC was diagnosed in 6 (3.6%) of 166 patients before treatment and in 3 patients (2.0%) 1 year later. The rate of patients who experienced PTSD symptoms related to BC decreased from 82.5 to 57.3% ( p  < 0.001), and the mean of BC‐related PTSD symptoms diminished from 3.1 to 1.7 ( p  < 0.001). Only university education significantly predicted the course of BC‐related PTSD symptom severity ( p  = 0.009). In 60 controls, no diagnosis of stress disorder, a rate of 18% women experiencing PTSD symptoms, and a mean of 0.4 PTSD symptoms ( p vs. patients <0.001) were found. Conclusions: Most newly diagnosed patients with BC experience PTSD symptoms, whereas full diagnoses of DSM‐IV stress disorder are rare. Symptoms diminish somewhat within 1 year furthered by university education but independently from mastectomy and chemotherapy. Throughout the year after diagnosis, having BC entails markedly increased PTSD symptom burden. Copyright © 2016 John Wiley & Sons, Ltd.